Seroprevalence of poliovirus antibodies before and after polio vaccine switch in 2012 and 2017 in Beijing - Juan Li; Zhujiazi Zhang; Herun Zhang; Maozhong Li; Xiaomei Li; Li Lu; Fang Huang; Jiang Wu (Human Vaccines & Immunotherapeutics, 2021)
In 2000, China was declared polio-free. However, in 2018, wild poliovirus (WPV) was still endemic in two of its neighboring countries, making WPV importation and outbreak alarming possibilities. This study documents the seroprevalence of poliovirus antibodies before and after the polio vaccine switch in 2012 and 2017 in Beijing. Cross-sectional population-based serologic surveys were conducted in 2012 and 2017 in Beijing. The study subjects were selected from 10 different age groups (<1, 1–4, 5–9, 10–14, 15–19, 20–24, 25–29, 30–34, 35–39, and ≥40 y) using a multi-stage-stratified sampling method. Neutralizing antibody titers against poliovirus serotypes 1 (P1), 2 (P2), and 3 (P3) were assayed by World Health Organization standards. The seropositive rates (SR) and geometric mean titer (GMT) of the neutralizing antibodies were 91.71% and 1:130.26, respectively, for P1, 94.09% and 1:113.39, respectively, for P2, and 88.78% and 1:79.65, respectively, for P3 before the switch in 2012, and 87.78% and 1:108.93, respectively, for P1, and 81.67% and 1:70.56, respectively, for P3 after the switch in 2017, with a statistically significant difference for P1 and P3 between 2012 and 2017. The neutralizing antibodies for all poliovirus serotypes differed among different age and vaccination groups in both 2012 and 2017. After switching polio vaccines twice in 2014 and 2016, the P1 and P3 polio antibody levels were lower in 2017 than in 2012. The P2 antibody levels were determined from the first dose of IPV. The seroprevalence of poliovirus antibodies after adjustment of the immunization schedule of the polio vaccine on January 1, 2020, must be further monitored.